Sterically Driven Pathways in Schiff Base Formation: tert-Butyl Effects on Hindered Imines - Cetin, M. Mustafa (Synthesis, 2025)
The ZnCl2/AcOH-mediated condensation of acenaphthenequinone with 2,4,6-tri-tert-butylaniline was explored to prepare a sterically demanding bidentate α-diimine ligand. Contrary to expectation, the reaction consistently afforded 1,2-bis[(2,4-di-tert-butylphenyl)imino]acenaphthene as the major product, together with a mono-substituted imino-ketone, while the fully substituted 1,2-bis[(2,4,6-tri-tert-butylphenyl)imino]acenaphthene was detected only in trace amounts. Spectroscopic analysis (nuclear magnetic resonance, UV/vis, Fourier transform infrared spectroscopy and single-crystal X-ray diffraction, supported by density functional theory calculations, showed that both ligands possess nearly identical electronic structures. However, the additional ortho tert-butyl group in the tri-substituted analogue induces severe steric congestion, twisting the aryl–imine geometry, diminishing π-conjugation, and facilitating acid-promoted tert-butyl elimination. In contrast, the di-substituted ligand adopts a near-planar geometry, enabling straightforward synthesis, crystallization, and full characterization. These results demonstrate that steric effects override electronic factors in dictating the reactivity and stability of highly hindered Schiff bases, providing mechanistic insight and practical design principles for the development of robust, sterically encumbered ligands in coordination chemistry and catalysis.
Keywords: Schiff bases; Steric hindrance; tert-Butyl elimination; Bidentate acenaphthenes; Sterically encumbered ligands